PENGENDALIAN PENYAKIT REBAH SEMAI DENGANTRICHODERMA DAN RHIZOBAKTERI PADA BAYAM CABUT - Heriyanto, Heriyanto (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2017)
A study was conducted to investigate the effect of antagonistic microorganisms and dose for the damping off control in spinach that were carried out in Banguntapan village, Banguntapan sub-district, Bantul district, from July to September 2016. The study used a complete randomized block design consisting of 5 treatments in the control of damping off, fungicide propineb, Rhizobakteri, Trichoderma sp, mixture of Trichoderma sp and Rhizobakeri with replication 4 times each treatment. The application is done by watering the land one day before the spinach seeds are planted, while the observation is done from the seeds planted until the plant is 30 days with 3 days interval. The results showed that the control treatment with the mixture of Rhizobacteria and Trichoderma sp concentration of 3 millilitres in 1 litter water showed effective results based on the analysis of the incubation period, the percentage of attacked plants and the intensity of the attack.